SCIENTIFIC PRODUCTION IN ENVIRONMENTAL LAW: A BIBLIOMETRIC STUDY IN SOUTH AMERICA - Cardoso, Flávio Manoel Coelho Borges; do Valle, Luciano; Sousa, Marcos de Moraes; Sousa, Lívia Aparecida Oliveira de Moraes (Revista de Ciências Jurídicas e Sociais da UNIPAR, 2023)
The theme of environmental law has been widely discussed in the world, being a very polemic area of law that can influence a country’s judiciary, economy, and public policies. However, what have researchers studied in this field? How has the research been conducted? These and other questions prompted us to conduct a bibliometric survey of studies on environmental law in South America. Thus, to better understand the theme and contribute to its state of the art, we searched scientific databases (SciELO and Portal Periódicos Capes) of articles on environmental law published in South American countries from 2010 through 2019. The results were tabulated using bibliometric indicators and analyzed using scientometry. Some of the results related to methodological indicators such as structural methodological flaws were found in the research. Another aspect identified in this study was the consequence of publication only in Portuguese, which makes the internationalization of journals and the knowledge produced in Brazil difficult. This is a quantitative method of data evaluation based on measures related to the publication of scientific papers. In this way, we hope to contribute to the development of future research on environmental law.